Using lanthanide ions in molecular bioimaging. (15th January 2015) - Amoroso, Angelo J.; Pope, Simon J. A.
Abstract : This review presents an accessible discussion of the application of trivalent lanthanide ions in both optical and magnetic resonance imaging. Abstract : Trivalent lanthanide ions offer remarkable opportunities in the design of bioimaging agents: this review presents an accessible discussion of their application in both optical and magnetic resonance imaging. Aspects of molecular design, control over key physical properties and biological compatibility are discussed in this context, together with developments and opportunities as responsive probes and in multimodal imaging.